THE ROLE OF INTERNATIONAL AGENCIES IN MANAGING ROHINGYA REFUGEES IN ACEH PROVINCE, INDONESIA: TOWARDS FUTURE SOLUTIONS - Kadir, M. Yakub Aiyub; Kesuma, T. Meldi; Siregar, M. Ridha; Halim, Hendra; Siregar, Muhammad Rizqi; Humaira, Radhia; Nisva, Raisa Ullya; Saddaq, Mizan (Universitas Syiah Kuala, 2024)
This study explores the management of Rohingya refugees in Aceh, focusing on the roles and responsibilities of key stakeholders with reference to United Nations High Commissiners for Refugees (UNHCR) and International Organsiasiton of Migration (IOM). Through social legal and emperical methods, including interviews and field observations, the article identifies challenges and potential solutions related to refugee management. The findings highlight the crucial role of UNHCR in providing protection and essential aid to Rohingya refugees, encompassing registration, documentation, and basic necessities. Simultaneously, IOM plays a pivotal role in facilitating orderly migration and advocating for human rights. The study also sheds light on a shift in local attitudes towards refugees, influenced by media misinformation and political motivations. Both organizations collaborate with the Indonesian government and local NGOs to address these issues, emphasizing the need for more comprehensive and long-term strategies. Recommendations include enhancing communication strategies, improving integration programs, and tackling the root causes of displacement. The study underscores the importance of a coordinated approach to support and safeguard Rohingya refugees.